The Application Of The Luftman Method Toward The Alignment Of Business Strategies And IT In Kelapa Dua Sub-district West Jakarta - Handayani, Rani Irma; Handayanna, Frisma; Sari, Fitri Ratna (Sinkron : jurnal dan penelitian teknik informatika, 2019)
The Kelapa Dua West Jakarta is a government agency that has to serve the community every day. In its operational activities, it requires Information Technology (IT) to complete daily operational tasks. Because of this, the west Jakarta sub-district of Kelapa Dua needs an appropriate IT management so that it can serve the community to the fullest. Good IT management is done by assessing the suitability between IT applications and organizational business processes. For this reason, the Luftman method is used to measure the alignment of Business and IT strategies by using six criteria namely Communications, Competency / Value Measurement, Governance, Partnership, Scope & Architecture, Skill. Overall, all the criteria and maturity of information technology strategies and business strategies in the kelurahan are still at level 2 or at the Commited level so that it can be said that there is no alignment between business strategies and IT strategies